The shapes of fancy : reading for queer desire in early modern literature - Varnado, Christine, 1980- (University of Minnesota Press, 2020)
"The Shapes of Fancy attempts to move the locus of queerness away from individual bodies or persons to scenes, plots, relations, and networks and, in doing so, redefine queer desire as an affective mode"--